Krajinska identiteta podeželskih naselij - Erdem Kaya, Meltem (Urbani izziv, 2024)
This research presents a methodology for assessing the landscape identity of rural settlements. The methodology evaluates landscape identity parameters as descriptive units and analyses landscape identity according to natural, built, socioeconomic, and sociocultural parameters at various scales. Turkey’s Aegean Region was selected as a case study for the research because of its rich rural pattern created by the combination of diverse geomorphology, a unique rural architectural character, climatic conditions, the rural economy, and sociocultural structures. The research presents several findings related to physical landscape identity. In addition, it shows important aspects of rural settlements through the lens of landscape identity and highlights the importance of identity-based approaches for sustainable rural development.